Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acs.macromol.0c01539
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Polymethacrylate Networks Containing Dynamic Dialkylamino Disulfide Linkages and Exhibiting Full Property Recovery

Abstract: Reprocessable polymer networks with dynamic covalent bonds exhibit thermoplastic-like properties at elevated processing temperatures while maintaining thermoset responses under service conditions, offering a sustainable solution to the recycling of conventional, permanently cross-linked polymers. Most studies on reprocessable networks that report full cross-link density recovery after recycling have focused on step-growth polymer networks; no study has previously reported full cross-link density recovery of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
105
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(130 citation statements)
references
References 56 publications
7
105
1
Order By: Relevance
“…This is considered the most suitable approach in terms of the simplification of recycling procedures, energy cost and the preparation of sustainable polymeric materials with a broad range of physico-chemical properties [ 134 ]. For example, recyclable catalyst-free polymethacrylate networks containing dynamic dialkylamino disulphide linkages (namely BiTEMPS) are synthesized by Bin Rusayyis et al [ 135 ]. The authors demonstrated that the reprocessable polymers with dynamic covalent bonds (both on step-growth polymer networks or based on full cross-link density recovery of reprocessable networks prepared from only monomers via addition polymerization) are characterized by thermoplastic-like properties.…”
Section: Discussionmentioning
confidence: 99%
“…This is considered the most suitable approach in terms of the simplification of recycling procedures, energy cost and the preparation of sustainable polymeric materials with a broad range of physico-chemical properties [ 134 ]. For example, recyclable catalyst-free polymethacrylate networks containing dynamic dialkylamino disulphide linkages (namely BiTEMPS) are synthesized by Bin Rusayyis et al [ 135 ]. The authors demonstrated that the reprocessable polymers with dynamic covalent bonds (both on step-growth polymer networks or based on full cross-link density recovery of reprocessable networks prepared from only monomers via addition polymerization) are characterized by thermoplastic-like properties.…”
Section: Discussionmentioning
confidence: 99%
“…Seeking for a simpler and more sustainable alternative towards longchain PA CANs, we focused on disulfides as an intrinsically reactive bond, 31,32 that can be activated under mild conditions. 33 Disulfides have been incorporated into urea, 34 urethane, 23,35,36 ester 4,37 and epoxy-based [38][39][40] networks, and have been combined with renewable building blocks such as diacids (succinic, adipic, sebacic), 4 castor oil 24,41 and epoxidized soybean oil, 42 leading to high-performance thermosets with impressive results regarding the ease of reprocessability and retainment of the mechanical properties after several reprocessing cycles.…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of their unique dissociation features, BiTEMPS were initially utilized as cross‐linking point within polymer networks to impart a thermally induced healing property. [ 15 ] Despite the elegant achievements based on the dynamic behavior of BiTEMPS derivatives, [ 16 ] such as the fusion of different cross‐linked polymers, [ 17 ] the topological rearrangement from linear to cyclic polymers, [ 18,19 ] and synthesis of end‐functionalized polymers, [ 20 ] to the best of our knowledge, the protocols utilized for the preparation of BiTEMPS containing polymers has been limited to conventional free‐radical or step‐growth polymerization approaches. Critically, due to the thermal lability of the BiTEMPS unit at temperatures above 80 °C, [ 14 ] previously reported polymerizations were essentially performed at ambient temperatures (Scheme 1B,C).…”
Section: Introductionmentioning
confidence: 99%